Social Construction of Politics and Religion:Study of 2024 Election Jingles in Surabaya City KPU Environment - Harrel Ciddan; Nur Khairun Nisa; Khuzaimah Khuzaimah (PT Pro Panoramic Solution, 2025)
The 2024 Election Jingle